Translating Arabic–Indonesian Captions on TikTok Social Media - Pramesti, Yunita Dwi; Gunawan, Fahmi; Anis, Muhammad Yunus (Arabiyatuna: Jurnal Bahasa Arab, 2023)
The present study aimed to analyze the captions of TikTok application from the perspective of translation techniques, methods, and ideology. As a matter of fact, although many scholars have researched the application of TikTok as a learning medium, less is known about it from the perspective of translation studies. The data of this study were derived from Arabic–Indonesian captions in the personal accounts of Abu Danah and Ahmad Al-Kurman, uploaded families from August to December 2021. The findings showcased the most dominant translation techniques found in 27 captions in the Abu Danah family account. 20 captions of Ahmad Al-Kurman were identified as a transposition translation technique. The translation method found in the caption of Abu Danah family account tended to use communicative methods and domestication ideology. In contrast, the translation method and ideology inclined to be used in the translation of Ahmad Al-Kurman's captions were free a translation method and the ideology of domestication. The study’s results concluded that the applications of transposition translation technique, the translation method tending to target languages, and the domestication ideology referred to translators' efforts to make it easier for readers to understand the translation results on TikTok media with its minimal space. Thus, short-form Arabic social media texts should be applied the free translation method based on domestication ideology in order to have a high level of readability.